1998
DOI: 10.1074/jbc.273.2.924
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of Endothelin Receptor B from Bovine Lungs Analyzed by Mass Spectrometry

Abstract: A new mild experimental approach for isolation of peptide membrane receptors and subsequent analysis of post-translational modifications is described. Endothelin receptors A and B were isolated on oligo(dT)-cellulose using N-(⑀-maleimidocaproyloxy)succinimide endothelin coupled to a protected (dA)-30-mer. This allowed a one-step isolation of the receptor from oligo(dT)-cellulose via variation solely of salt concentration. The identity of the receptor was confirmed by direct amino acid sequencing of electroblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…The reason for this is unknown. Differential cell-type-specific posttranslational modification of the ET B receptor molecule may account for the lack of endothelial binding, because the epitope used for immunization lies in close proximity to a potential glycosylation site at amino acid residue 60 (Roos et al 1998). However, there are no studies addressing this issue in vascular smooth muscle and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unknown. Differential cell-type-specific posttranslational modification of the ET B receptor molecule may account for the lack of endothelial binding, because the epitope used for immunization lies in close proximity to a potential glycosylation site at amino acid residue 60 (Roos et al 1998). However, there are no studies addressing this issue in vascular smooth muscle and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of Polyadenylated Met-Lys-Bradykinin-Met-Lys-bradykinin derivatized with EMCS at the ⑀-NH 2 group of Lys 2 was prepared by a synthesis similar to that used recently to prepare an analogous endothelin derivative (12). 1 mg (400 nmol) of Met-Lys-bradykinin was dissolved in 400 l of 35% acetonitrile, 0.05% trifluoroacetate, further diluted with 50 mM sodium borate and 0.015% Triton X-305, pH 8.2, and a 10-fold excess (4 mol) of the heterobifunctional cross-linker EMCS dissolved in 200 l of acetonitrile was added.…”
Section: Methodsmentioning
confidence: 99%
“…45 Other studies, where the putative N-glycosylation site of ETB was mutated, did not reveal any modification of the expression of ETB at cell surface, binding to ET1 or coupling to signaling pathways. 46,47 Moreover, Roos et al 48 found, by mass spectrometry approach, that ETB, extracted from bovine lung, was not glycosylated in its N-terminal domain. These results indicate that the glycosylation of ETB does not influence the structure and function of the receptor, and has very few chances to play a role in the discriminating properties of rendomab-B4 toward CHO-ETB and UACC-257 cells.…”
Section: (C and D) Living Uacc-257 Cells Were Incubated For 2 H At 4 mentioning
confidence: 99%